Comparison of the Flue Gas Emission Values of a Traditional Designed Biomass Boiler with the Specified Emission Standards - Fáczán, Erika; Megyeri, Gábor; Vojtela, Tibor; Béres, András (Journal of Central European Green Innovation, 2022)
Reducing emissions of various air pollutants is needed to achieve cleaner and healthier air quality in all EU countries. The National Air Pollution Reduction Programme sets out pollution reduction targets of 55% for particulate matter (PM), 73% for sulphur dioxide, 58% for non-methane volatile organic compounds and 66 % for nitrogen oxides, among other air pollutants, by 2030 compared to the 2005 reference year. The household sector is one of the areas most responsible for the emission of the main air pollutants linked to human activity. Within this, household solid biomass combustion is particularly important as a widely used heating method in Hungary. In this paper, we show how traditional boilers pollute the environment by measuring the results of a given boiler. Furthermore, the study describes how the specific boiler's air pollutant emissions and energy performance occurred. Finally, the research found that traditional boilers cannot meet strict emission standards, so their replacement and further development may be justified.